Security supervision and management : the theory and practice of asset protection - Davies, Sandi J.; Hertig, Christopher A.; Gilbride, Brion P. (Butterworth-Heinemann is an imprint of Elsevier, 2015)
Security Supervision and Management, Fourth Edition, fills the basic training needs for security professionals who want to move into supervisory or managerial positions. Covering everything needed from how to work with today's generation security force employees to the latest advances in the security industry, Security Supervision and Management, Fourth Edition, shows security officers how to become a more efficient and well-rounded security professional. Security Supervision and Management, Fourth Edition, is also the only text needed to prepare for the Certified in Security Supervision and Management (CSSM) designation offered by International Foundation for Protection Officers (IFPO).